Al-Lughah al-Arabiyah wa al-Tahaddiyat al-Mustaqbaliyah fi Ashri al-Raqminah/ The Arabic Language and Future Challenges in The Era of Digitization - Ammar Ali Madi (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
The objectives of the study focus on identifying the challenges facing the Arabic language in how to preserve belonging and identity in the digital age and thus preserve the Arab-Islamic culture, and formulate the shape of the Arab human society, as well as identifying the growing role of the Arabic language on the knowledge map as a basic pillar of knowledge of all kinds. And through the different centuries, in order to absorb the challenges and harness them to solve developmental problems, and prepare a distinguished human elite technically and artistically to face the challenges of innovations in the third millennium, and keep pace with creativity in the digital age, in addition to clarifying the issues and problems facing the digital transformation of Arab intellectual production in the global space and the extent of the capabilities of this Transformation, as well as identifying Arab strategic initiatives and projects in the field of digitization and thus developing and enriching Arabic digital content on the Internet, in addition to that the current study seeks through achieving its previous objectives to come out with a set of recommendations that contribute to the advancement of the Arabic language and its computerization in the age of digitization, and enrichment of content Digital Arabic.المستخلص: تتركز أهداف الدراسة في التعرف على التحديات التي تواجه اللغة العربية في كيفية الحفاظ على الانتماء والهوية في العصر الرقمي وبالتالي المحافظة على الثقافة العربية الإسلامية ، وصياغة شكل المجتمع الإنساني العربي ،كذلك التعرف على الدور المتنامي للغة العربية على الخريطة المعرفية باعتبارها ركيزة أساسية للمعرفة على اختلاف أنواعها وعبر القرون المختلفة ، وذلك لاستيعاب التحديدات وتسخيرها لحل المشكلات التنموية ، وإعداد نخبة بشرية متميزة تقنياً وفنياً لمواجهة تحديات التجديدات في الألفية الثالثة ، ومسايرة الإبداع في العصر الرقمي ، هذا فضلاً عن توضيح القضايا والإشكاليات التي تواجه التحول الرقمي للإنتاج الفكري العربي في الفضاء الكوني ومدى إمكانات هذا التحول ، كذلك التعرف على المبادرات والمشاريع الإستراتيجية العربية في مجال الرقمنة وبالتالي تطوير وإثراء المحتوى الرقمي العربي على العنكبوتية ، هذا إلى جانب أن الدراسة الحالية تسعى من خلال تحقيق أهدافها السابقة للخروج بمجموعة من التوصيات التي تسهم في النهوض باللغة العربية وحوسبتها في عصر الرقمنة ، وإثراء المحتوى العربي الرقمي.